2016
DOI: 10.1038/ncomms10446
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of coherent propagating spin waves by pure spin currents

Abstract: Utilization of pure spin currents not accompanied by the flow of electrical charge provides unprecedented opportunities for the emerging technologies based on the electron's spin degree of freedom, such as spintronics and magnonics. It was recently shown that pure spin currents can be used to excite coherent magnetization dynamics in magnetic nanostructures. However, because of the intrinsic nonlinear self-localization effects, magnetic auto-oscillations in the demonstrated devices were spatially confined, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 37 publications
3
80
0
Order By: Relevance
“…However, the emission of spin waves with sub‐micrometric wavelength is challenging due to the slow spatial decay of the field and the high impedance of the antennas as the size approaches nanoscale dimensions . Ferromagnetic nanostructures, spin‐transfer torque, spin‐orbit torques, spin currents, magnetoelastic coupling, and multiferroic heterostructures are alternative methods used for spin‐wave generation; however, they do not provide a straightforward control of the wavefront and beam shape. Other methods for spatially controlling the spin‐wave propagation include using the natural anisotropy of the spin‐wave dispersion, or physically micro/nanopatterning the spin‐wave medium, but their flexibility and scalability to multi‐beam configurations is limited.…”
mentioning
confidence: 99%
“…However, the emission of spin waves with sub‐micrometric wavelength is challenging due to the slow spatial decay of the field and the high impedance of the antennas as the size approaches nanoscale dimensions . Ferromagnetic nanostructures, spin‐transfer torque, spin‐orbit torques, spin currents, magnetoelastic coupling, and multiferroic heterostructures are alternative methods used for spin‐wave generation; however, they do not provide a straightforward control of the wavefront and beam shape. Other methods for spatially controlling the spin‐wave propagation include using the natural anisotropy of the spin‐wave dispersion, or physically micro/nanopatterning the spin‐wave medium, but their flexibility and scalability to multi‐beam configurations is limited.…”
mentioning
confidence: 99%
“…We note however that the proposed gates have inputs (spin-waves with a magnetic field) and outputs (only spin-waves) that are different so that they require additional spin-wave-to-current converters, which are definitely detrimental for practical use. One may combine spin-wave logic with spin-transfer torque [29] or electric-field magnetization switching technique [30] to remove or at least simplify this additional part.…”
mentioning
confidence: 99%
“…40 Pure spin currents have direct applications in spin transfer torque based magnetic switching, [41][42][43][44][45] spin torque oscillators 35,37,[46][47][48][49] and domain wall manipulation. 50,51 In addition, some interesting effects of the pure spin currents have been studied, for instance, the suppression of the Kondo singlet, 52 the generation of coherent propagating spin waves in magnetic circuits, 53 and the excitation of dynamic modes in a microscopic insulating Yttrium Iron Garnet disks. 54 It is shown that an efficient pure-spin-current injection can be used to realize the magnetization switching of a nano-scale ferromagnetic particle and measurements of room temperature spin Hall effect as well.…”
Section: Introductionmentioning
confidence: 99%